Credit risk and commercial bank performance: evidence from ASEAN - Bao, Yi Lew; Wei, Theng Lau (Human Resource Management Academic Research Society, 2022)
This study aims to examine the relationship between credit risk and the performance of commercial banks in the ASEAN (Association of Southeast Asian Nations) region. 113 commercial banks across Malaysia, Singapore, Thailand, Philippines, and Vietnam are covered for analysis purposes. The study quantifies the credit risk using three commonly seen metrics i.e. capital adequacy ratio, loan to deposit ratio, and non-performing loan. Capital adequacy ratio and loan to deposit ratio could present the riskiness of the funding strategy of banks, while non-performing loan represents the overall customer payments past due as the potential result of risk-taking behaviour. Panel data analysis covering the years 2016-2020 for the above-mentioned bank sample is employed in examining the relationships. The result indicates that all the above metrics have a significant relationship with commercial bank performance, proxied by return on equity and return on assets, largely consistent with the underlying expectations. While the risk-taking behaviour may enhance the return measure of profitability, it would at the same time expose a bank to the downside risk as reflected by a higher level of non-performing loans. The study could provide empirical evidence to the managers and regulators in the region for a better understanding of banks' risks in formulating better policies to foster prudent management and decision making.